2009
DOI: 10.1245/s10434-009-0827-4
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of Circumferential Resection Margins in Esophageal Carcinoma

Abstract: BackgroundIn esophageal cancer, circumferential resection margins (CRMs) are considered to be of relevant prognostic value, but a reliable definition of tumor-free CRM is still unclear. The aim of this study was to appraise the clinical prognostic value of microscopic CRM involvement and to determine the optimal limit of CRM.MethodsTo define the optimal tumor-free CRM we included 98 consecutive patients who underwent extended esophagectomy with microscopic tumor-free resection margins (R0) between 1997 and 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…Consistent with the reported literature, CRM invasion did contribute to shorter survival in ESCC patients, either in surgery group or in nCCRT-surgery group (Tables 3,4) (18,30,31). When divided into sub-groups I, II and III (≤3, 3-5, >5 cm), the CRM invasion rates in surgery group raised from 3.2% to 4.5% and then 31.3% progressively, however, they remained around 10% in nCCRT-surgery group (Table 5).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with the reported literature, CRM invasion did contribute to shorter survival in ESCC patients, either in surgery group or in nCCRT-surgery group (Tables 3,4) (18,30,31). When divided into sub-groups I, II and III (≤3, 3-5, >5 cm), the CRM invasion rates in surgery group raised from 3.2% to 4.5% and then 31.3% progressively, however, they remained around 10% in nCCRT-surgery group (Table 5).…”
Section: Discussionsupporting
confidence: 89%
“…However, they were not able to detect any significant differences in regards to CRM involvement (p = 0.192) [32]. In another study by Pultrum et al [33], the type of surgery did not influence the extension of CRM involvement (p = 0.693) at all. …”
Section: Surgical Approachmentioning
confidence: 82%
“…Few studies have investigated the direct impact on margin involvement. Two studies found higher positive CRMs after transhiatal resections while another failed to demonstrate any differences between surgical approaches [23,31,33]. A higher rate of CRM involvement might be due to failed en bloc resections, which are known to improve patients' prognosis [44].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of the oesophageal CRM has been demonstrated in many studies4 8, 10 11, 14, 15, 16 25, 26, 27, 28. A large multicentre study in 2016 9 demonstrated that the CAP definition of CRM positivity was independently predictive of poor survival, whereas a meta‐analysis29 suggested that, although the CAP definition identified the highest‐risk group, the RCP definition encompassed patients still at risk of poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…The College of American Pathologists (CAP) defines a positive CRM as tumour at the cut margin (TAM), which has been advocated in some studies4, 5, 6, 7, 8, 9, whereas the Royal College of Pathologists (RCP) defines a positive CRM as tumour within 1 mm, preferred in other studies10, 11, 12, 13. Some studies have found the CRM to be independently prognostically significant4 7, 9 10, 13, 14, 15, 16, and others have not5 6, 11 12, 17, 18, 19. A positive margin may increase the likelihood of locoregional and systemic tumour recurrence9 20, although it is unclear whether the latter is simply a reflection of a larger, more advanced tumour.…”
Section: Introductionmentioning
confidence: 99%